A Novel Legumain-Like Protease in Macrobrachium nipponense: Identification, Characterization, and Function Analysis in Ovary Maturation - Jiang, Sufei; Xiong, Yiwei; Zhang, Wenyi; Zhu, Junpeng; Cheng, Dan; Gong, Yongsheng; Wu, Yan; Qiao, Hui; Fu, Hongtuo (Frontiers in Endocrinology, 2022)
Legumain, also called aspartic endopeptidase (AEP), is a member of the cysteine protease family and is involved in various physiological processes. In this study, we analyzed the characteristics of a novel legumain-like (named Mn-Lel) in the female oriental river prawn, Macrobrachium nipponense, which is involved in ovary maturation. The Mn-Lel is 1,454 bp in length, including a 1,290-bp open reading frame that encodes 430 amino acids. qPCR analysis indicated that Mn-Lel is specifically highly expressed in the hepatopancreas and ovaries of female prawns. It is rarely expressed in embryogenesis, weakly expressed in early larval development stages, and then significantly increased after metamorphosis, which indicated that Mn-Lel is not a maternal gene and mainly plays a role in adults. During the different ovarian stages, Mn-Lel expression in the hepatopancreas had no obvious rules, while its expression in the ovaries had a significant peak in stage III. In situ hybridization studies revealed that Mn-Lel is localized in the oocyte of the ovary. Changes in the gonadosomatic index confirmed the inhibitory effects of Mn-Lel dsRNA on ovary maturation. These results suggest that Mn-Lel has a key role in promoting ovary maturation.